Some Necessary Options of Learning English Comparing with Other Foreign Languages - Pulatova Shakhzoda Khaydarovna; Tolibova Nodira Nosirovna (Genius Journals, 2022)
In this article, we will look at the intricacies of learning two languages at the same time.
Keywords: travel; working; education; interfere